Why first-level health workers fail to follow guidelines for managing severe disease in children in the Coast Region, the United Republic of Tanzania - Nicholas D Walter; Thomas Lyimo; Jacek Skarbinski; Emmy Metta; Elizeus Kahigwa; Brendan Flannery; Scott F Dowell; Salim Abdulla; S Patrick Kachur (The World Health Organization, 2009)
OBJECTIVE: To determine why health workers fail to follow integrated management of childhood illness (IMCI) guidelines for severely ill children at first-level outpatient health facilities in rural areas of the United Republic of Tanzania. METHODS: Retrospective and prospective case reviews of severely ill children aged < 5 years were conducted at health facilities in four districts. We ascertained treatment and examined the characteristics associated with referral, conducted follow-up interviews with parents of severely ill children, and gave health workers questionnaires and interviews. FINDINGS: In total, 502 cases were reviewed at 62 facilities. Treatment with antimalarials and antibiotics was consistent with the diagnosis given by health workers. However, of 240 children classified as having "very severe febrile disease", none received all IMCI-recommended therapies, and only 25% of severely ill children were referred. Lethargy and anaemia diagnoses were independently associated with referral. Most (91%) health workers indicated that certain severe conditions can be managed without referral. CONCLUSION: The health workers surveyed rarely adhered to IMCI treatment and referral guidelines for children with severe illness. They administered therapy based on narrow diagnoses rather than IMCI classifications, disagreed with referral guidelines and often considered referral unnecessary. To improve implementation of IMCI, attention should focus on the reasons for health worker non-adherence.